2006
DOI: 10.1124/jpet.106.110262
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Blockade of Electron Transport during Ischemia Protects Mitochondria and Decreases Myocardial Injury following Reperfusion

Abstract: Cardiac mitochondria sustain damage during ischemia and reperfusion, contributing to cell death. The reversible blockade of electron transport during ischemia with amobarbital, an inhibitor at the rotenone site of complex I, protects mitochondria against ischemic damage. Amobarbital treatment immediately before ischemia was used to test the hypothesis that damage to mitochondrial respiration occurs mainly during ischemia and that protection of mitochondria during ischemia leads to decreased cardiac injury with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
206
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(228 citation statements)
references
References 37 publications
17
206
2
Order By: Relevance
“…We recently demonstrated that nitrite augments tolerance to I/R injury via the modulation of mitochondrial electron transfer (25). In addition, the inhibition of complex I by nitrite has previously been shown to decrease ROS production by the mitochondria and limit oxidative protein damage (31)(32)(33). Taken together, we here give unequivocal evidence that nitrite modulates mitochondrial function during anoxia and show that this regulation depends on the presence of myoglobin.…”
Section: Discussionsupporting
confidence: 63%
“…We recently demonstrated that nitrite augments tolerance to I/R injury via the modulation of mitochondrial electron transfer (25). In addition, the inhibition of complex I by nitrite has previously been shown to decrease ROS production by the mitochondria and limit oxidative protein damage (31)(32)(33). Taken together, we here give unequivocal evidence that nitrite modulates mitochondrial function during anoxia and show that this regulation depends on the presence of myoglobin.…”
Section: Discussionsupporting
confidence: 63%
“…As shown previously, partial inhibition of complex I during ischemic incubation would protect mitochondria from damage after reperfusion (42,43). Therefore, it is possible that the reversible deactivation of complex I in the absence of oxygen may function as a protective valve and reduce the burst of respiration downstream of complex I upon tissue reoxygenation.…”
Section: Discussionmentioning
confidence: 97%
“…Another possible mechanism for H 2 S protective action on mitochondrial function may lie in its ability to modulate cellular respiration during reperfusion. The inhibition of mitochondrial respiration has been shown (26,27) to protect against MI-R injury by limiting the generation of reactive oxygen species and diminishing the degree of mitochondrial uncoupling leading to decreased infarct size and preserved function. The accumulation of evidence that mitochondrial function and structure was preserved after myocardial infarction in mice treated with H 2 S was further corroborated by the decreased activation of caspase-3 and a decrease in the number of TUNEL positive nuclei, suggesting that H 2 S was capable of inhibiting the progression of apoptosis after MI-R injury.…”
Section: Discussionmentioning
confidence: 99%